Catalyst powder and preparation method and application of carbon nanotube of catalyst powder
The catalyst is prepared in one step by rapid decomposition method, and the problems of large grain size and uneven distribution in the prior art are solved, efficient and low-cost catalyst preparation are achieved, and the performance and yield of carbon nanotubes are improved. It is suitable for lithium-ion batteries and other fields.
Patent Information
- Application Number
- CN202410744911.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-03-04
AI Technical Summary
The existing catalyst preparation methods lead to large grain sizes and uneven distribution of the catalyst, which affects the performance and yield of carbon nanotubes, and is complex in the process and high in cost.
The rapid decomposition method is used to directly prepare an aqueous solution containing catalytically active elements using metal salts. By atomizing and adjusting the ratio of active elements and support elements, a sheet-like catalyst with uniform particle size distribution and small grain size is prepared in one step.
The efficient preparation of catalysts is achieved. The prepared carbon nanotubes have high specific surface area, low resistance and high yield, and have better performance than commercial conductive agents. They are suitable for lithium-ion batteries and other fields.
Smart Images

Figure CN119549149A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing catalyst powder and is used for the preparation and application of carbon nanotubes, belonging to the technical field of catalyst and carbon nanotube preparation. Background Art
[0002] Conductive agents are used as electron transport media in lithium-ion batteries. The conductivity of the material is the primary criterion for selection. Secondly, the size of the conductive agent should be smaller than the particle size of the active material. Currently, the commercial conductive agents widely used are all nano-sized. In addition, the amount of conductive agent required to build a good conductive network should be as small as possible, and the electrochemical properties of the conductive agent should be stable, and no harmful reactions should occur with other materials during the battery charging and discharging process. The preparation cost of the conductive agent should not be too high.
[0003] Carbon nanotubes (CNTs) have excellent mechanical, electrical, thermal and optical properties due to their unique microstructure, and are therefore widely used in high-performance composite materials, electronics, catalysis, energy conversion and storage, etc. In lithium-ion batteries in particular, CNTs have unique ballistic electron conduction effects, resistance to electromigration, high conductivity (up to 105S / m) and flexibility. Using them directly as the matrix material of the electrode or adding them as a conductive additive to the active electrode material can significantly improve the electron / ion transport capacity and mechanical properties of the electrode.
[0004] The preparation of carbon nanotubes by vapor phase chemical deposition depends on the composition and structure of the catalyst. The preparation method of the catalyst plays an important role in the performance of carbon nanotubes. At present, the methods for preparing catalysts mainly include precipitation method, impregnation method, sol-gel method, etc. The prepared catalyst grain size is large and unevenly distributed, resulting in different performance and quality of the prepared carbon nanotubes, which is not conducive to the excellent performance of carbon nanotubes and has low efficiency.
[0005] The rapid decomposition method is a method developed from the preparation of transparent electrodes for solar cells. When the metal salt solution enters the high-temperature atmosphere in the form of fine droplets, the solvent evaporates and the metal salt decomposes immediately, and then the solid phase precipitates due to supersaturation, thereby directly obtaining nanopowders; or the solution is sprayed into the high-temperature atmosphere to dry, and then heat-treated to form powders. The rapid decomposition method is widely used in the preparation of metal materials, inorganic non-metallic materials, and functional materials such as superconductors, optics, magnets, and electrodes because of its simple preparation method and easy preparation of powders with small particle size and good dispersion.
[0006] In recent years, more and more researchers have devoted themselves to using this method to prepare catalyst powders for synthesizing carbon nanotubes. For example, patent CN 105873679 B discloses a catalyst for synthesizing multi-walled carbon nanotubes, a method for preparing the catalyst, and multi-walled carbon nanotubes synthesized by the catalyst. It reports a method for synthesizing a large specific surface area layer catalyst, and uses the catalyst to synthesize multi-walled carbon nanotubes with a high specific surface area. In this patent, the active component and the carrier are composed of three or more metal elements. More metal elements are used in the catalyst preparation process, which increases the cost, and the yield of the catalyst is low. It is still difficult to mass-produce high-quality carbon nanotubes. CN 114558583 A discloses a method for synthesizing ultrafine catalyst powders, and publishes a method for synthesizing a spherical catalyst with a particle size of less than 5μm and a large specific surface area. The carbon nanotubes prepared by the method can reach a specific surface area of 600 to 1000m 2 / g. In the patent, during the catalyst preparation process, the solution is prepared using a two-step complexation method, which results in a long solution preparation time and a harsh solution preparation method. In addition, multiple substances such as citric acid, ethylenediaminetetraacetic acid, ammonia water, and urea are introduced during the catalyst preparation process, which not only increases the cost but also makes the process relatively complicated. Summary of the invention
[0007] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a catalyst powder, directly using metal salts to prepare an aqueous solution containing catalytically active elements, so that the spatial distribution of metal ions in the solution is relatively uniform, and by adjusting the ratio of active elements and carrier elements, the temperature of rapid decomposition and other factors, a lamellar catalyst with uniform particle size distribution, small grain size and good catalytic activity is prepared in one step. The process flow for preparing the catalyst is simple, easy to operate, and low in cost. The catalyst is applied to the preparation of carbon nanotubes to prepare array-type carbon nanotubes with high specific surface area, high yield and low resistance. The prepared carbon nanotubes are used as conductive agents and applied to lithium-ion batteries, and their performance is significantly better than commercial conductive agents. In view of the above-mentioned purpose, the present invention first provides a method for preparing a catalyst powder, comprising the following steps:
[0008] (1) dissolving an active metal salt and a carrier metal salt in a solvent to form a mixed solution;
[0009] (2) atomizing the mixed solution in step (1) to form fine droplets, microdroplets or microspheres which enter the decomposition chamber for decomposition and collect the powder;
[0010] Wherein, the active metal salt is selected from iron salt and / or cobalt salt, and the carrier metal salt is selected from magnesium salt and / or aluminum salt.
[0011] In one embodiment of the present invention, the iron salt is selected from at least one of ferric chloride (FeCl3), ferric nitrate (Fe(NO3)3), ferric sulfate (Fe2(SO4)3) or related iron salt products, the cobalt salt is selected from at least one of cobalt nitrate (Co(NO3)2), cobalt sulfate (CoSO4), cobalt chloride (CoCl2), cobalt bromide (CoBr2), cobalt iodide (CoI2), cobalt fluoride (CoF2) or related cobalt salt products, the magnesium salt is selected from at least one of magnesium chloride (MgCl2), magnesium sulfate (MgSO4), magnesium carbonate (MgCO3), magnesium nitrate (Mg(NO3)2) or related magnesium salt products, and the aluminum salt is selected from at least one of aluminum nitrate (Al(NO3)3), aluminum sulfate (Al2(SO4)3), aluminum chloride (AlCl3) or related aluminum salt products.
[0012] In one embodiment of the present invention, in step (1), the chemical formula of the active metal salt and the carrier metal salt is Fe a Co b Mg c Al d In the above chemical formula, a, b, c, and d represent the molar fraction of each element, respectively, 0≤a≤10, 0≤b≤10, 0≤c≤20, and 0≤d≤20.
[0013] In one embodiment of the present invention, in step (1), in the mixed solution, the total mass fraction of the active metal salt and the carrier metal salt is 40-90%.
[0014] In one embodiment of the present invention, in step (1), the solvent includes at least one of water, alcohols (methanol, ethanol, propanol, butanol, ethylene glycol, glycerol, etc.), N,N-dimethylformamide, and N-methylpyrrolidone.
[0015] In one embodiment of the present invention, in step (2), the pumping speed of the mixed solution is 20-200 L / h.
[0016] In one embodiment of the present invention, in step (2), the atomization method includes forming the mixed solution into fine droplets through two-fluid, or rotary, or fixed, or orifice tube nozzle or ultrasonic atomization, or forming droplets or microspheres through microfluidic technology, and the decomposition temperature is 400-1000°C.
[0017] In one embodiment of the present invention, in step (2), the atomization method is that the mixed solution passes through a two-fluid nozzle, and under the drive of a carrier gas, fine droplets are formed and enter the decomposition chamber. The carrier is air or an inert gas (nitrogen, argon, etc.), and the pressure of the carrier gas is 0.2 to 1.2 MPa.
[0018] In one embodiment of the present invention, in step (2), the decomposition temperature is 400-1000°C, preferably 400-700°C, more preferably 500-700°C.
[0019] In one embodiment of the present invention, in step (2), the atomization method is that the mixed solution is formed into droplets or microspheres through microfluidic technology, the processing volume is 25 to 300 ml / h of the core phase, and a single-channel or multi-channel microfluidic precision manufacturing platform is used.
[0020] In one embodiment of the present invention, in step (2), the mixed solution is an aqueous phase, and the oil phase is an HFE-based droplet-forming oil.
[0021] In one embodiment of the present invention, in step (2), the pumping pressure is 0 to 8 bar, and the curing method is photo-crosslinking curing, evaporation curing or thermal crosslinking curing.
[0022] The present invention also provides a catalyst powder prepared by the method.
[0023] In one embodiment of the present invention, for the prepared catalyst powder, in the powder X-ray diffraction analysis, if the chemical composition is Fe a Co b Mg c Al d , then at the diffraction angle 2θ = 36° ± 2° there is a characteristic peak of CoAl2O4, and at the diffraction angle 2θ = 43° ± 2° there is a characteristic peak of MgO; if the chemical composition is Fe a Mg c , then at the diffraction angle 2θ = 43° ± 2° there is a characteristic peak of MgO, and at the diffraction angle 2θ = 62° ± 2° there is a characteristic peak of MgFe3O4; if the chemical composition is Co b Al d , then there is a characteristic peak of CoAl2O4 at the diffraction angle 2θ=36°±2°, and there are characteristic peaks of Co2AlO4 at the diffraction angles 2θ=59°±2° and 2θ=65°±2°.
[0024] The present invention also provides a method for preparing carbon nanotubes using the above catalyst powder. The carbon nanotubes can be prepared using a fixed bed reactor, a fluidized bed reactor, a rotary kiln reactor, etc. as reactors for preparing the carbon nanotubes.
[0025] In one embodiment of the present invention, a fixed bed reactor is used to prepare carbon nanotubes, and the method comprises the following steps:
[0026] S1. Take the catalyst powder, put it into a quartz tube furnace with a diameter of 80 mm, introduce nitrogen, and heat the tube furnace to raise its temperature to 300 ° C;
[0027] S2. Continue to increase the temperature to 660°C at 15°C / min through nitrogen and hydrogen;
[0028] S3. Stop introducing hydrogen and introduce nitrogen and ethylene to grow carbon nanotubes for 30 to 60 minutes. After the reaction is completed, cool down under nitrogen protection. After cooling, collect the product in the tubular furnace to obtain carbon nanotubes.
[0029] In one embodiment of the present invention, in step S1, the amount of catalyst powder added is 0.05-0.4 g.
[0030] In one embodiment of the present invention, in step S1, the flow rate of nitrogen is 200-800 mL / min, and the heating rate of the tube furnace is 5-15° C. / min.
[0031] In one embodiment of the present invention, in step S2, the flow rate of nitrogen is 200-800 mL / min, and the flow rate of hydrogen is 200-800 mL / min.
[0032] In one embodiment of the present invention, in step S2, the flow rate ratio of nitrogen to hydrogen is 1:1.
[0033] In one embodiment of the present invention, in step S3, the flow rate of nitrogen is 200-800 mL / min, and the flow rate of ethylene is 100-400 mL / min.
[0034] In one embodiment of the present invention, in step S3, the flow rate ratio of nitrogen to ethylene is 2:1.
[0035] In one embodiment of the present invention, carbon nanotubes are prepared using a fluidized bed, and the method comprises the following steps:
[0036] ① Introduce an inert gas (any one of helium (He), neon (Ne), argon (Ar), krypton (Kr), and xenon (Xe)) into the reactor; turn on the fluidized bed preheater and raise the temperature to 590°C; the temperature of the upper, middle, and lower sections of the fluidized bed reactor is controlled at 660°C.
[0037] ② After reaching the working temperature, add the catalyst, introduce hydrogen, and continue to introduce inert gas for reduction reaction.
[0038] ③ After the reduction is completed, the introduction of hydrogen is stopped, and a carbon source (ethylene or propylene) is introduced to prepare carbon nanotubes in a fluidized bed reactor in multiple stages.
[0039] ④ After the reaction is completed, the inert gas is continuously introduced, the pulse and discharge pneumatic valves are opened, and the fluidized bed material is collected to obtain carbon nanotubes.
[0040] In one embodiment of the present invention, in step ①, the flow rate of the inert gas is 1.0 to 550 L / min, and the heating rate of the fluidized bed reactor is 5 to 15° C. / min.
[0041] In one embodiment of the present invention, in step ②, the amount of catalyst powder added is 1-10 g, and the flow rate ratio of the inert gas to the hydrogen is 1:1.
[0042] In one embodiment of the present invention, in step ③, the flow rate ratio of the inert gas to the carbon source is 2 to 3:1.
[0043] In one embodiment of the present invention, in step ③, the flow rate of the inert gas is 3.0 to 1000 L / min, and the flow rate of the carbon source is 1 to 350 L / min.
[0044] In one embodiment of the present invention, in step ④, the flow rate of the inert gas is 20 to 300 L / min.
[0045] The invention also provides a carbon nanotube prepared by the method.
[0046] In one embodiment of the present invention, for the prepared carbon nanotubes, in the Raman spectrum, at 1560±150cm -1 The maximum peak intensity in the range of 1310±150cm -1 When the maximum peak intensity in the range of is set to D, the G / D ratio is 1.0 to 4.0.
[0047] In one embodiment of the present invention, the prepared carbon nanotubes have at least 200 m 2 / g BET specific surface area.
[0048] In one embodiment of the present invention, the half maximum width (FWHM) of the prepared carbon nanotubes is between 2.5 and 7.5 in XRD characterization.
[0049] The present invention also provides an application of the carbon nanotube in a lithium ion battery.
[0050] In one embodiment of the present invention, the application includes use as an electrode of a lithium-ion battery.
[0051] In one embodiment of the present invention, a method for preparing an electrode of a lithium-ion battery comprises the following steps: using LiMn2O4 (LMO) as an active material for the positive electrode, carbon nanotubes (CNTs) as a conductive additive, polyvinylidene fluoride (PVDF) as a binder, polyvinyl pyrrolidone (PVP) as a dispersant, N-methylpyrrolidone (NMP) as a solvent, the diaphragm model is Celgard 2400, and the electrolyte is 1.0M lithium hexafluorophosphate (LiPF6) prepared by ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and ethylene carbonate (EC) in a ratio of 1:1:1.
[0052] Beneficial Effects of the Invention
[0053] (1) The catalyst preparation method of the present invention is used to prepare flaky catalyst powder particles with uniform particle size distribution in one step by a rapid decomposition method. The catalyst preparation process and composition are simple, the catalyst activity is high, and the prepared carbon nanotubes are bundled carbon nanotubes with consistent orientation and are easy to disperse. When preparing the solution, nitrate and water are directly used, which is simple to operate. The metal cations in the solution form coordination compounds, and the spatial distribution of the metal ions in the solution is relatively uniform. During the rapid decomposition process, the metal ions in the small droplets are not easy to agglomerate due to the spatial effect, and it is easier to form grains with smaller grain size.
[0054] (2) The multi-walled carbon nanotubes synthesized using the catalyst prepared by the preparation method of the present invention have a diameter close to that of single-walled carbon nanotubes (SWNTs), the number of walls of the multi-walled carbon nanotubes is 3 to 10 and they are in a very uniform state, and the specific surface area of the multi-walled carbon nanotubes is large, which can reach 200-1000 m 2 / g, thus exhibiting very high conductivity.
[0055] (3) The carbon nanotubes grown using the catalyst of the present invention have a purity of more than 99.5%, the mass of the prepared carbon nanotubes can be up to 323 times the mass of the catalyst, the diameter of the prepared carbon nanotubes is 3 to 10 nm, and the powder resistance is as low as 40 mΩ·cm.
[0056] (4) The carbon nanotubes of the present invention are used as a conductive agent in lithium-ion batteries. The prepared conductive agent slurry has good dispersibility and conductivity, effectively reduces battery polarization and charge transfer impedance, and improves battery cycle reversible capacity and capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 The XRD diagrams of the five catalysts obtained in Examples 1 to 7 of the present invention are shown in FIG.
[0058] Figure 2 These are SEM images of the five catalysts obtained in Examples 1 to 7 of the present invention.
[0059] Figure 3 This is the SEM image of the catalyst in Comparative Example 1 of the present invention.
[0060] Figure 4 This is the SEM image of the catalyst in Comparative Example 2 of the present invention.
[0061] Figure 5 These are the XRD and SEM images of the catalyst obtained by the precipitation method in Comparative Example 3 of the present invention.
[0062] Figure 6 The SEM images of carbon nanotubes prepared by using the catalysts in Examples 1 to 7 of the present invention are shown.
[0063] Figure 7 The SEM image of the carbon nanotubes obtained in Comparative Example 1 of the present invention is
[0064] Figure 8 This is a TEM image of the carbon nanotubes obtained in Comparative Example 2 of the present invention.
[0065] Fig. 9 This is a SEM image of the carbon nanotubes obtained in Comparative Example 3 of the present invention.
[0066] Fig.10 These are Raman images of the carbon nanotubes in Examples 1 to 7 of the present invention.
[0067] Fig.11 This is the XRD diagram of the carbon nanotubes in Example 1 of the present invention.
[0068] Fig.12 The electrochemical performance diagram of carbon nanotubes prepared using the catalysts in Example 4 and Comparative Example 3. DETAILED DESCRIPTION
[0069] Test method:
[0070] SEM test: SEM analysis was performed using Thermo Fisher Apreo 2C HiVac;
[0071] XRD test: XRD test was carried out using German Bruker D8FOCUS;
[0072] TEM test: Titan G260-300 from FEI Company of the United States was used for testing;
[0073] Specific surface area test: Use JW BK122W specific surface area analyzer for testing;
[0074] Raman spectroscopy: Raman spectroscopy was performed using Thermo Scientific DXR3;
[0075] Electrochemical performance: tested using Autolab electrochemical workstation and blue electric test system;
[0076] Carbon nanotube yield: the mass of carbon nanotubes prepared by the catalyst divided by the mass of the catalyst used.
[0077] Example 1
[0078] The method for preparing catalyst powder comprises the following steps:
[0079] Weigh 1.9 kg of ferric nitrate nonahydrate, 1.12 kg of cobalt nitrate hexahydrate, 6.4 kg of aluminum nitrate nonahydrate, and 21.88 kg of magnesium nitrate hexahydrate, dissolve them in 10 kg of pure water, and stir to dissolve to form a solution. The prepared chemical formula is Fe a Co b Mg c Al d . Wherein, a+b=10, c+d=20. The prepared solution was passed through a multi-channel microfluidic droplet / microsphere manufacturing platform, with a processing capacity of 300 ml / h for the core phase, 2% HFE7500 (produced by Drop-Surf) for the oil phase, a pumping pressure of 6.4 bar, a curing method of UV light cross-linking curing, and a decomposition temperature of 700°C entering the decomposition chamber.
[0080] The method for preparing carbon nanotubes comprises the following steps:
[0081] The present invention uses a fixed bed reactor to prepare carbon nanotubes, comprising the following steps:
[0082] ① Take 0.4g of catalyst powder, put it into a quartz tube furnace with a diameter of 80mm, introduce nitrogen at a flow rate of 500mL / min, and heat it to 300℃ at a rate of 15℃ / min;
[0083] ② After the temperature reaches 300℃, keep the nitrogen flow rate unchanged, introduce hydrogen flow rate at 500mL / min, and continue to increase the temperature to 660℃ at 15℃ / min;
[0084] ③ When the temperature reaches 660°C, stop introducing hydrogen, keep introducing nitrogen at 400mL / min, and introduce ethylene at a flow rate of 200mL / min to grow carbon nanotubes for 60min. After the reaction is completed, cool down under nitrogen protection, collect the product in the tube furnace after cooling, and obtain carbon nanotubes.
[0085] Example 2
[0086] The difference between Example 2 and Example 1 is that when preparing the catalyst, the prepared solution is sprayed into the reaction chamber through a two-fluid atomizer driven by air carrier gas. The pumping speed of the solution is 20L / h, the air carrier gas pressure is 0.2Mpa, and the decomposition temperature is 400°C.
[0087] When preparing carbon nanotubes, a fluidized bed is used, and ethylene is used as a carbon source, which includes the following steps:
[0088] ① Argon (Ar) was passed through the reactor at a flow rate of 5 L / min; the fluidized bed preheater was turned on and the temperature was raised to 590°C at a rate of 15°C / min; the upper, middle and lower sections of the fluidized bed reactor were heated at a rate of 15°C / min and the temperature was controlled at 660°C.
[0089] ② After reaching the working temperature, add 4 g of catalyst, introduce hydrogen at 3 L / min, and continue to introduce argon at 3 L / min, and the reaction time is 5 min.
[0090] ③ After the reduction is completed, stop introducing hydrogen and introduce ethylene. In reaction stages 1 to 2, the argon flow rate is 3 L / min, and the ethylene flow rates are 0.5 and 1 L / min, respectively. The reaction time for each stage is 5 min; in reaction stages 3 to 4, the argon flow rate is 4 L / min, and the ethylene flow rates are 1.5 and 2 L / min, respectively. The reaction time for each stage is 5 min; in reaction stage 5, the argon flow rate is 5 L / min, the ethylene flow rate is 2.5 L / min, and the stage reaction time is 10 min.
[0091] ④ After the reaction is completed, argon gas is continuously introduced at 20 L / min, and the pulse backflush and discharge pneumatic valves are opened to collect the fluidized bed material to obtain carbon nanotubes.
[0092] Example 3
[0093] The difference between Example 3 and Example 2 is that when preparing carbon nanotubes, the carbon source is changed to propylene.
[0094] Example 4
[0095] The difference between Example 4 and Example 2 is that when preparing the catalyst powder, the decomposition temperature is changed to 700°C.
[0096] Example 5
[0097] The difference between Example 5 and Example 2 is that when preparing the catalyst powder, the decomposition temperature is changed to 1000°C.
[0098] Example 6
[0099] The difference between Example 6 and Example 4 is that when preparing the catalyst powder, the chemical formula Fe a Co b Mgc Al d In the equation, the molar amounts of iron and magnesium elements are changed to a=c=0.
[0100] Example 7
[0101] The difference between Example 7 and Example 4 is that when preparing the catalyst powder, the chemical formula Fe a Co b Mg c Al d In the equation, the molar amounts of cobalt and aluminum elements are changed to b=d=0.
[0102] Comparative Example 1
[0103] The difference between Comparative Example 1 and Example 1 is that the method for preparing the catalyst powder is different.
[0104] Preparation method of catalyst powder: Mg(NO3)2·6H2O and A1C13·6H2O are added to 100 ml of water, and then stirred so that the sum of the molar numbers of Al and Mg becomes 16, and Fe(NO3)2·9H2O and Co(NO3)2·6H2O are added, and then stirred so that the sum of the molar numbers of Fe and Co becomes 5. Then, the above mixture is droplet-sprayed and calcined at a temperature of 400 to 900° C. to obtain a catalyst.
[0105] Comparative Example 2
[0106] The difference between Comparative Example 2 and Example 1 is that the method for preparing the catalyst powder is different.
[0107] The method for preparing catalyst powder comprises the following steps:
[0108] (1) Using a 1000 mL beaker, weigh 8.1 g of ferric nitrate nonahydrate, 5.8 g of cobalt nitrate hexahydrate, 102.6 g of magnesium nitrate hexahydrate, 30 g of aluminum nitrate nonahydrate, 585 g of pure water, 0.71 g of ammonium heptamolybdate tetrahydrate, and 99.9 g of anhydrous citric acid, and stir to dissolve; then heat in a water bath at 92° C., install a stirring blade, set the speed to 400 rpm for stirring, and concentrate the solution in an open state for 2 hours to obtain a concentrated solution;
[0109] (2) using a 2000 mL beaker, weighing 83.6 g of ethylenediaminetetraacetic acid, 493 g of ammonia water (25 wt.%), and 4.2 g of urea in sequence, and stirring and dissolving them at room temperature to form an ethylenediaminetetraacetic acid solution; mixing the concentrated solution of step (1) and the ethylenediaminetetraacetic acid solution, installing a paddle, setting the speed to 400 rpm, and stirring at room temperature for 30 min to fully mix them and obtain a mixed solution;
[0110] (3) The mixed solution of step (2) is injected into the atomizer of the spray tower through a peristaltic pump at a flow rate of 100 mL / min, 300 L / min compressed air is used as the carrier gas, the decomposition temperature of the heating furnace is set to 450° C., and the spray pyrolysis is performed for 8 minutes to obtain the ultrafine catalyst powder.
[0111] Comparative Example 3
[0112] The difference between Comparative Example 3 and Example 1 is that the method for preparing the catalyst powder is different.
[0113] Comparative Example 3: The catalyst was prepared by precipitation method, and the specific implementation process was as follows:
[0114] S1. Solution A: Add 5000g of water to a 20L beaker, add 1241g of cobalt nitrate, 2977g of aluminum nitrate, and stir to dissolve; Solution B: Add 2040g of water to a 5L beaker, then add 131g of anhydrous sodium carbonate, 346g of sodium bicarbonate, and stir to dissolve;
[0115] S2. Place solution A in a water bath at 60°C. Stir at 250 rpm and drip solution B into solution A via a peristaltic pump for 4 hours. After the titration, measure the pH value of the solution to be between 8.2 and 9.2. Then turn off the stirring and keep the solution at 60°C for 4.5 hours.
[0116] S3. After aging, the filtrate is filtered and washed until the pH value is 7.
[0117] S4. Put the washed filter cake into a muffle furnace, heat it from room temperature to 630℃, and keep it warm for 4 hours. After natural cooling, sieve it through 80 mesh for later use.
[0118] The performance of the catalysts prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were tested. The test results are as follows: Figures 1 to 11 and as shown in Table 1. Figure 1 The XRD patterns of the catalyst samples in Examples 1 and 4-5 are shown. Through XRD analysis of the samples in the examples, it is found that CoAl2O4, MgO, Co3O4, MgFe3O4 and other substances are generated in the samples of Examples 1 and Examples 2-5 (XRD patterns of Examples 2-3 are omitted). The XRD analysis of Examples 4-5 shows that the crystal structure of the samples is better with the increase of reaction temperature, while in Example 5, the catalyst has a tendency to turn into cobalt blue due to the high reaction temperature, so the catalyst activity decreases. In Example 6, three substances, Co3O4, Co2AlO4 and CoAl2O4, are formed, among which more cobalt and aluminum bimetallic oxides are generated. Figure 2The figure shows the SEM of the catalyst sample in the example. Through SEM analysis, Example 1 uses microfluidic technology to form a hollow spherical catalyst with a narrow particle size distribution, which is quite different from the sheet catalyst prepared by using a two-fluid nozzle in other examples.
[0119] Figure 3 and Figure 4 The SEM images of the catalysts prepared in Comparative Example 1 and Comparative Example 2 are respectively. It can be seen from the SEM that the catalyst prepared in Comparative Example 1 has a plate-like appearance, while the catalyst prepared in Comparative Example 2 has a spherical appearance.
[0120] Figure 5 The XRD and SEM of the catalyst sample in Comparative Example 3 are shown. The sample in Comparative Example 11 was analyzed by XRD, and CoCo2O4 was generated in the sample. This may be because the Al ions formed precipitation first in the precipitation method and were covered by the Co ions that precipitated later, so the Al substance was not shown. Through SEM analysis, the catalyst prepared by the precipitation method showed a flaky structure and was evenly distributed.
[0121] The performance of the catalysts prepared in Examples and Comparative Examples 1 to 3 was tested. The test results are as follows: Figures 6 to 10 and as shown in Table 1. Figure 6 The SEM images of the carbon nanotubes (CNTs) prepared in Examples 1 to 7 are shown. Through SEM analysis, it can be observed that the prepared carbon nanotubes all appear as array tubes, and the carbon nanotubes are arranged in a relatively orderly manner. Figures 7 to 9 The figure shows the SEM of carbon nanotubes (CNTs) prepared by the catalyst in the comparative example. Through SEM analysis, it can be observed that the prepared carbon nanotubes are agglomerated in large quantities, and most of them are in a state of entangled carbon nanotubes.
[0122] Fig.10 The Raman test results of the carbon nanotubes prepared by the catalysts in Examples 1 to 7 are shown. According to the test results, the Raman IG / / D of the carbon nanotubes prepared by the catalysts in the examples is between 2.76 and 3.68, and the Raman IG / / D of the carbon nanotubes prepared by the better catalysts is as high as 3.68.
[0123] Fig.11 The XRD pattern of the carbon nanotubes prepared by the catalyst in Example 1 is shown. Since the XRD patterns of the carbon nanotubes in Examples 2 to 7 are similar to those in Example 1, only the characterization results of Example 1 are shown here. According to the test results, the prepared carbon nanotubes have obvious characteristic peaks of carbon materials at around 25°, and the half-peak width FWHM is 2.5 to 7.5 when the baseline 2θ of the half-peak width is between 12° and 40°.
[0124] Fig.12The electrochemical performance test of carbon nanotubes prepared by two kinds of catalysts in Example 4 and Comparative Example 3 is shown. It can be clearly concluded that the carbon nanotubes obtained in Example 4 of the present invention have lower AC impedance, higher cycle specific capacity, higher discharge specific capacity and higher coulombic efficiency.
[0125] Example 4 is significantly better than the carbon nanotube performance shown in other examples and comparative examples in terms of yield, Raman IG / ID intensity, etc. Compared with the examples, the carbon nanotubes prepared by all comparative example catalysts are closer to wound tubes, and the carbon nanotubes prepared by the catalyst in the example are array tubes, with a yield of up to 323 times, and Raman IG / ID is also as high as 3.68, and the electrochemical performance is more excellent.
[0126] Table 1 Summary of catalyst and carbon nanotube product tests
[0127]
[0128] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a catalyst powder, characterized in that: The following steps are involved: (1) dissolving an active metal salt and a carrier metal salt in a solvent to form a mixed solution; (2) atomizing the mixed solution in step (1) to form fine droplets, microdroplets or microspheres which enter the decomposition chamber for decomposition and collect the powder; Wherein, the active metal salt is selected from iron salt and / or cobalt salt, and the carrier metal salt is selected from magnesium salt and / or aluminum salt.
2. The preparation method according to claim 1, characterized in that: In step (1), the iron salt is selected from at least one of iron chloride, iron nitrate, iron sulfate or related iron salts thereof, the cobalt salt is selected from at least one of cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt bromide, cobalt iodide, cobalt fluoride or related cobalt salts thereof, the magnesium salt is selected from at least one of magnesium chloride, magnesium sulfate, magnesium carbonate, magnesium nitrate or related magnesium salts thereof, the aluminum salt is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum chloride or related aluminum salts thereof, and the chemical formula composed of the active metal salt and the carrier metal salt is Fe a Co b Mg c Al d In the chemical formula, a, b, c, and d represent the molar fraction of each element, respectively, 0≤a≤10, 0≤b≤10, 0≤c≤20, and 0≤d≤20.
3. The preparation method according to claim 1, characterized in that: In step (1), in the mixed solution, the total mass fraction of the active metal salt and the carrier metal salt is 40-90%, and the solvent includes at least one of water, alcohols, N,N-dimethylformamide, and N-methylpyrrolidone.
4. The preparation method according to claim 1, characterized in that: In step (2), the atomization method includes forming the mixed solution into fine droplets through two-fluid, or rotary, or fixed, or orifice tube nozzle or ultrasonic atomization, or forming droplets or microspheres through microfluidic technology, and the decomposition temperature is 400-1000°C.
5. The preparation method according to claim 4, characterized in that: In step (2), the atomization method is that the mixed solution passes through a two-fluid nozzle, and under the drive of the carrier gas, fine droplets are formed and enter the decomposition chamber. The pumping speed of the mixed solution is 20-200L / h, the carrier is air or inert gas, and the pressure of the carrier gas is 0.2-1.2Mpa.
6. Catalyst powder prepared according to the method according to any one of claims 1 to 5.
7. The catalyst powder according to claim 6, characterized in that In powder X-ray diffraction analysis, if the chemical composition is Fe a Co b Mg c Al d , then at the diffraction angle 2θ = 36° ± 2° there is a characteristic peak of CoAl2O4, and at the diffraction angle 2θ = 43° ± 2° there is a characteristic peak of MgO; if the chemical composition is Fe a Mg c , then at the diffraction angle 2θ = 43° ± 2° there is a characteristic peak of MgO, and at the diffraction angle 2θ = 62° ± 2° there is a characteristic peak of MgFe3O4; if the chemical composition is Co b Al d , then there is a characteristic peak of CoAl2O4 at the diffraction angle 2θ=36°±2°, and there are characteristic peaks of Co2AlO4 at the diffraction angles 2θ=59°±2° and 2θ=65°±2°.
8. A method for preparing carbon nanotubes using the catalyst powder according to claim 7, characterized in that: The following steps are involved: S1. Take the catalyst powder, put it into a quartz tube furnace with a diameter of 80 mm, introduce nitrogen, and heat the tube furnace to raise its temperature to 300 ° C; S2. Continue to increase the temperature to 660°C at 15°C / min through nitrogen and hydrogen; S3. Stop introducing hydrogen and introduce nitrogen and ethylene to grow carbon nanotubes for 30 to 60 minutes. After the reaction is completed, cool down under nitrogen protection. After cooling, collect the product in the tubular furnace to obtain carbon nanotubes.
9. The preparation method according to claim 8, characterized in that: In step S1, the amount of catalyst powder added is 0.05-0.4 g, the flow rate of nitrogen is 200-800 mL / min, and the heating rate of the tubular furnace is 5-15°C / min. In step S2, the flow rate of nitrogen is 200-800 mL / min, the flow rate of hydrogen is 200-800 mL / min, and the flow rate ratio of nitrogen to hydrogen is 1:1; in step S3, the flow rate of nitrogen is 200-800 mL / min, the flow rate of ethylene is 100-400 mL / min, and the flow rate ratio of nitrogen to ethylene is 2:
1.
10. The carbon nanotubes prepared according to the method of claim 8 or 9.
11. The carbon nanotube according to claim 10, characterized in that: In Raman spectroscopy, at 1560±150cm -1 The maximum peak intensity in the range of 1310±150cm -1 When the maximum peak intensity in the range of is set to D, the G / D ratio is 1.0 to 4.
0.
12. The carbon nanotube according to claim 10 or 11, characterized in that: In the BET specific surface area, they all have at least 200m 2 / g of BET specific surface area, and in XRD characterization, its half-peak width FWHM is between 2.5 and 7.
5.
13. Use of the carbon nanotube according to any one of claims 10 to 12 in a lithium ion battery, the use comprising using the carbon nanotube as an electrode of the lithium ion battery.
Citation Information
Patent Citations
Catalysts for the synthesis of multi-walled carbon nanotubes, methods for preparing the catalysts, and multi-walled carbon nanotubes synthesized from the catalysts.
CN105873679B
Synthesis method of superfine catalyst powder
CN114558583A